BARRIERS TO PHYSICAL ACTIVITY IN RECENTLY DIAGNOSED TYPE 2 DIABETES MELLITUS PATIENTS: A QUALITATIVE STUDY - Yulia Kurniawati; Ninuk Dian Kurniawati; Ririn Probowati (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2020)
Background: Physical activity as one of diabetes management plays important role in maintaining glycemic control. Not all diabetics are doing adequate physical activity. Especially for recently diagnosed type 2 Diabetes Mellitus patients with the characteristic haven’t adopt diabetes management properly.Objectives: The aim of this study to reveal the barriers in physical activity that faced by recently diagnosed type 2 Diabetes Mellitus patients.Methods: Qualitative study with phenomenological approach was conducted in 10 recently diagnosed type 2 Diabetes Mellitus patients in Primary Health Care Kedungdoro and Asemrowo, Surabaya. The participants were selected based on inclusion criteria, namely patients aged 25-45 years old, under 6 months diagnosed, spoke in Indonesian or Javanese well. The exclusion criteria were patients with complication. Semi-structured in-depth interviews guided by interview guideline was conducted to obtain the information about barrier in physical activity. There were six questions in interview guideline. Then data from interview was analyzed by Colaizzi method.Results: Two themes were emerged as barriers in physical activity namely time expenditure and health literacy. Participants’ time expenditure refers to the limited time in doing physical activity, namely obligation to others and lack of spare time. Health literacy refers to the ability in searching and using health information. The barrier in health literacy aspect namely physical activity substitute and different information that got from others.Conclusion: The barriers of physical activity were problem in time flexibility, activity substitute, and need for straightening various information. Using media technology and involving family to promote and remind the physical activity can be suggested. Keywords: Barriers, Diabetes Mellitus Type 2, Recently Diagnosed, Physical Activity